(untitled) - Damrosch, David (New York, 2010)
Volume 2C (20th Century) of 6-volume splits of parent volumes. .Too often, debate in the "culture wars" of recent years have assumed that there is an essential conflict between study of classics of earlier centuries and contemporary, multicultural writings. The Longman Anthology of British Literature shows that either/or choices do not need to be made: British literary culture has always been characterized by a dynamic mix of cultures -- English, Irish, Welsh, and Scottish. The great classics of British literature have come out of a rich cultural ferment that has always included popular as well as elite productions, women's writing as well as men's, secular as well as religious writing, regional as well as metropolitan perspectives, here seriously represented for the first time in a major anthology. --This text refers to an out of print or unavailable edition of this title.
Keywords: English literature,Great Britain,Văn học Anh,Anh Quốc; Civilization,Nền văn minh; 20th century,20th century,Thế kỷ 20,Thế kỷ 20